On the Theory of Finance for Privately Held Firms - James S. Ang (Journal of Small Business Finance, 1992)
This paper is a first attempt at differentiating the problems of finance of the privately held small businesses from their larger counterparts. Small businesses, though not concerned with the problems and opportunities associated with publicly traded firms, have different types of complexities, such as shorter expected life, presence of estate tax, intergenerational transfer problems, and prevalence of implicit contracts. Some standard problems like agency and asymmetric information are also more complex. The relatively high transaction costs faced by small businesses in all types of financial decisions also preclude a sizable subset of available choices.
Keywords: G32; L25; G35; G31; 650; Finance; Theory of Finance; Privately-Held; Small Business